Technology enriched teaching simulations - Welsh, Megan E.; Mastrup, Kayce L. (Educational technology research and development, 2025)
This paper explores the potential of new, technology enriched teaching simulations (Simulations) to support learning. Using the principles of evidence-centered design (ECD; Mislevy et al., Measurement: Interdisciplinary Research and Perspectives. 1:3–62, 2003), we provide a roadmap for the design of: (a) simulation-based assessments (SBAs) and (b) instruction-focused Simulations, and argue that the ECD framework can foster coherence between an instructional simulation and the larger educational efforts it is designed to support. This approach also helps ensure that Simulations target intended cognitions that might not otherwise be developed. Using teacher preparation as an example, we discuss how Simulations can be used to create focused approximations of practice opportunities that are tightly controlled and that target difficult to capture aspects of teaching, including responsiveness to student ideas through teacher noticing. Using our own work developing Simulations to foster teacher noticing skills, the paper outlines the stages of an ECD approach to Simulation design and also the role of various stakeholders in development processes. We conclude by highlighting the affordances of incorporating Simulations into educational efforts, both as instructional and assessment tools, and identify areas in need of further study.